First report of the presence of Pseudoterranova sp. in the body cavity of salmon (Salmo salar) from the Baltic Sea - Nadolna-Ałtyn Katarzyna; Podolska Magdalena; Pawlak Joanna (Fisheries & Aquatic Life)
Despite salmon (Salmo salar L.) being an important fish in the Baltic Sea ecosystem and its fisheries, knowledge about the parasite fauna of this top predator is scarce. The Anisakidae nematodes (Anisakis spp., Pseudoterranova spp., Contracaecum sp.) found in Baltic Sea fish species are zoonotic parasites that are hazardous to human health. Due to the marked increase in the numbers of grey seal (Halichoerus grypus), the definitive host of Contracaecum sp. and Pseudoterranova spp., increased dispersion of these parasites has been observed in recent years. The aim of our study was to investigate salmon caught in Polish marine waters for the presence of Anisakidae nematodes. Parasitological inspection of the body cavities of 89 individual salmon was conducted in 2012 and revealed the presence of a Pseudoterranova sp. L3 larva. The presence of the parasite is reported here for the first time in the muscle tissue of salmon from the Baltic Sea. The presence of Anisakidae nematodes in commercially important fish species may have implications for human health since these parasites pose a risk of anisakidosis.